2001
DOI: 10.1103/physrevlett.87.255501
|View full text |Cite
|
Sign up to set email alerts
|

Nuclear Inelastic X-Ray Scattering of FeO to 48 GPa

Abstract: The partial density of vibrational states has been measured for Fe in compressed FeO (wüstite) using nuclear resonant inelastic x-ray scattering. Substantial changes have been observed in the overall shape of the density of states close to the magnetic transition around 20 GPa from the paramagnetic (low pressure) to the antiferromagnetic (high pressure) state. The results indicate that strong magnetoelastic coupling in FeO is the driving force behind the changes in the phonon spectrum of FeO. The paper present… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
57
0

Year Published

2003
2003
2017
2017

Publication Types

Select...
5
3

Relationship

6
2

Authors

Journals

citations
Cited by 75 publications
(63 citation statements)
references
References 28 publications
(37 reference statements)
6
57
0
Order By: Relevance
“…NRIXS signals originate from particular resonant nuclei only, and this complete isotope selec tivity is truly unique among techniques for the study of lattice vibrations. For example, materials surrounding the sample that do not contain resonant nuclei produce no unwanted background, and this feature now permits experiments under extreme pressuretemperature conditions that were impossible before (Lubbers et al, 2000a;Mao et al, 2001Mao et al, , 2004bStruzhkin et al, 2001;Lin et al, 2003Lin et al, , 2004aLin et al, , 2004bLin et al, , 2005bShen et al, 2004;Papandrew et al, 2004;Kobayashi et al, 2004;Zhao et al, 2004). Details on the scattering mechanisms and methodology for NRJXS and SMS have been published elsewhere Sturhahn, 2004).…”
Section: Experimental Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…NRIXS signals originate from particular resonant nuclei only, and this complete isotope selec tivity is truly unique among techniques for the study of lattice vibrations. For example, materials surrounding the sample that do not contain resonant nuclei produce no unwanted background, and this feature now permits experiments under extreme pressuretemperature conditions that were impossible before (Lubbers et al, 2000a;Mao et al, 2001Mao et al, , 2004bStruzhkin et al, 2001;Lin et al, 2003Lin et al, , 2004aLin et al, , 2004bLin et al, , 2005bShen et al, 2004;Papandrew et al, 2004;Kobayashi et al, 2004;Zhao et al, 2004). Details on the scattering mechanisms and methodology for NRJXS and SMS have been published elsewhere Sturhahn, 2004).…”
Section: Experimental Methodsmentioning
confidence: 99%
“…The addition of light elements such as silicon, oxygen, sulfur, and hydrogen to iron also has significant effects on the shear proper ties (Machova and Kadeckova, 1977;Struzhkin et al, 2001;Lin et al, 2003Lin et al, ,2004aMao et al, 2004b;Jacobsen et al, 2004). Sev eral experiments have been performed to understand the crystal chemistry of these complex systems (Irifune, 1994;Kesson et al, 1995;Wood and Rubie, 1996;Hirose et al, 1999;Frost and Langenhorst, 2002), and they have shown that even though most of the iron in mantle materials is divalent (Fe2+), a significant amount of trivalent iron (Fe3+) was determined for aluminumbearing (Mg,Fe)SiO3-perovskite (McCammon, 1997).…”
Section: Introductionmentioning
confidence: 99%
“…From the low-energy region of each phonon DOS, Debye sound velocity can be derived. 1 2 3 4 5 6 7 8 9 10 11 12 13 14 15 16 17 18 19 20 21 22 23 24 25 26 27 28 29 30 31 32 33 34 35 36 37 38 39 40 41 42 43 44 45 46 47 48 49 50 51 52 53 54 55 56 57 58 59 60 Phonon DOS has been determined for a number of iron compounds and alloys: FeO [519,520], FeS [521], Fe-Ni [522], Fe-Si alloys [287,522], FeH [523], Fe3S [524], Fe3C [525][526][527], Fe2O3 [528], (Mg,Fe)O [497], and (Mg,Fe)SiO3 enstatite [529]. For nanocrystalline Fe, large distortions were found in its phonon DOS [530], showing a lifetime broadening at high energies and an enhancement in its phonon DOS at energies below 15 meV.…”
Section: Phonon Density Of Statesmentioning
confidence: 99%
“…Examples of sound velocity determination using NRIXS include: Fe [63,297,517,518], FeO [519,520], FeS [521], Fe-Ni [522], Fe-Si alloys [287,522], FeH [523], Fe3S [524], Fe3C [525][526][527], Fe2O3 [528], and (Mg,Fe)O [497]. The Debye parabola is best constrained at the low-energy limit, and a resolution of better than 2 meV is 1 2 3 4 5 6 7 8 9 10 11 12 13 14 15 16 17 18 19 20 21 22 23 24 25 26 27 28 29 30 31 32 33 34 35 36 37 38 39 40 41 42 43 44 45 46 47 48 49 50 51 52 53 54 55 56 57 58 59 60 therefore essential in NRIXS for approaching that limit.…”
Section: Sound Velocitiesmentioning
confidence: 99%
“…This technique provides the phonon excitation spectrum as seen by the probe nuclei, 3,4,5 and in most cases one can extract the partial vibrational frequency distribution, a function often referred to as the partial phonon density of states (PDOS). The NRIXS method has been applied to various materials, e.g., thin films and multilayers, 6,7,8 nanoparticles, 9,10 crystals with impurities, 11 organic molecules, 12,13,14,15 proteins, 16,17 samples under high pressures, 18 and samples of geophysical interests. 19,20 Most of these samples are compounds, and, while the obtained PDOS gives only part of the lattice dynamics, the low-energy portion of the PDOS provides the Debye sound velocity of the whole sample.…”
mentioning
confidence: 99%